Learning Microsoft Word 2010 - Ellwood, Tim.; Safari eBooks ([S.l.] : InfiniteSkills, 2010)
"In this Beginners Microsoft Word 2010 tutorial video, author Tim Ellwood guides you through learning and using the worlds most used document creation software. Starting with the basics, you will quickly learn how to efficiently and effectively create documents of all kinds. You begin by learning where the basic tools are, the ribbon, the toolbar, help and other handy tools. The tutorial video then presses forward to cover editing text, formatting text, inserting images, mail merge, proofing, printing, and much much more. The expert instruction of Microsoft trainer Tim Ellwood breaks each task down into easy to learn pieces that anyone can understand and follow. By the completion of this computer based training video, you will be fully proficient in creating, editing, and distributing documents using the powerful and popular Microsoft Word 2010."--Resource description page.
Title and publication information from resource description page (viewed July 19, 2011).
Presenter, Tim Ellwood.
Keywords: Microsoft Word; Word processing; Electronic books